(untitled) (Contemporary Journal of Social Science Review, 2025)
Natural disasters such as earthquakes, floods, droughts, and epidemics cause severe human, economic, and environmental losses. This study explores the major factors and impacts of natural disasters and highlights preventive and remedial measures in the light of the teachings of Prophet Muhammad (ﷺ). Using a qualitative analytical approach, the research examines Prophetic guidance related to human responsibility, moral conduct, environmental care, patience, and social solidarity. The study finds that although natural disasters occur due to natural processes, human negligence, injustice, and environmental misuse intensify their effects. The teachings of the Prophet (ﷺ) provide a comprehensive framework for disaster prevention and management by promoting ethical behavior, cleanliness, charity, preparedness, and reliance on Allah. The study concludes that integrating Prophetic teachings with modern disaster management strategies can help build resilient and morally responsible societies.